Short-term fructose feeding alters tissue metabolic pathways by modulating microRNAs expression both in young and adult rats - Petito, Giuseppe; Giacco, Antonia; Cioffi, Federica; Mazzoli, Arianna; Magnacca, Nunzia; Iossa, Susanna; Goglia, Fernando; Senese, Rosalba; Lanni, Antonia (Frontiers in Cell and Developmental Biology, 2023)
Dietary high fructose (HFrD) is known as a metabolic disruptor contributing to the development of obesity, diabetes and dyslipidemia. Children are more sensitive to sugar than adults due to the distinct metabolic profile, therefore it is especially relevant to study the metabolic alterations induced by HFrD and the mechanisms underlying such changes in animal models of different ages. Emerging research suggests the fundamental role of epigenetic factors such as microRNAs (miRNAs) in metabolic tissue injury. In this perspective, the aim of the present study was to investigate the involvement of miR-122-5p, miR-34a-5p and miR-125b-5p examining the effects induced by fructose overconsumption and to evaluate whether a differential miRNA regulation exists between young and adult animals. We used young rats (30 days) and adult rats (90 days) fed on HFrD for a short period (2 weeks) as animal models. The results indicate that both young and adult rats fed on HFrD exhibit an increase in systemic oxidative stress, the establishment of an inflammatory state, and metabolic perturbations involving the relevant miRNAs and their axes. In the skeletal muscle of adult rats, HFrD impair insulin sensitivity and triglyceride accumulation affecting the miR-122-5p/PTP1B/P-IRS-1(Tyr612) axis. In liver and skeletal muscle, HFrD acts on miR-34a-5p/SIRT-1:AMPK pathway resulting in a decrease of fat oxidation and an increase in fat synthesis. In addition, liver and skeletal muscle of young and adult rats exhibit an imbalance in antioxidant enzyme. Finally, HFrD modulates miR-125b-5p expression levels in liver and white adipose tissue determining modifications in de novo lipogenesis. Therefore, miRNA modulation displays a specific tissue trend indicative of a regulatory network that contributes in targeting genes of various pathways, subsequently yielding extensive effects on cell metabolism.